A Three–Part Framework for Self–Regulated Personality Development across Adulthood. Issue 3 (May 2014) - Hennecke, Marie; Bleidorn, Wiebke; Denissen, Jaap J. A.; Wood, Dustin
Recently, researchers interested in personality development have begun to acknowledge the roles of motivation and self–regulation for why traits change across adulthood. We propose three preconditions under which individuals may change their own levels of a personality trait through self–directed efforts. Firstly, individuals need to desire changing their trait–related behaviours either as an end in itself or in order to achieve other goals. Secondly, they need to consider behavioural changes feasible and be able to implement the desired changes. Thirdly, behavioural changes need to become habitual in order to constitute a stable trait. After elaborating on these three conditions, we review evidence attesting to the importance of motivation and self–regulation for trait development. We conclude with a discussion of the mutual interdependence of traits and goals, as well as the limits of self–regulated personality change. From our framework, we derive why personality changes across adulthood tend to be small to medium only, namely because they may require that all three preconditions for self–regulated personality change are fulfilled. We provide reasons for why people might not view change as desirable, feasible or fail to maintain it over time. Finally, we propose ideas for potential study designs to research self–regulated personality change. Copyright © 2014 European Association of Personality Psychology